Impact of house prices on household carbon emissions - Cong, Ying; Wang, Yanxu; Wu, Yanlin (Frontiers in Environmental Science, 2023)
Carbon emissions generated by household activities are one of the important factors of climate warming, and carbon emission reduction in household consumption will be an important part of energy conservation in the future. Taking household consumption as the starting point, the impact of housing price on carbon emissions of household consumption was studied. It is found that the rise in house prices has a significant promoting effect on household consumption carbon emissions, the wealth effect of house-owned households is greater than the crowding out effect, in houseless households, the substitution effect is greater than the crowding out effect, the impact of rising house prices on various household consumption carbon emissions is different, the impact on the carbon emissions of living materials such as clothing and residence is greater, and the impact on hedonistic consumption carbon emissions is small. Further research found that the rise in housing prices had the strongest effect on carbon emissions from household consumption in the central region, and the home-owning households in the east responded more to the increase in housing prices than in the west, while the houseless households showed that the promotion effect on the west was greater than that in the east. Urban dwellers with homes and rural households without homes are more sensitive to rising house prices.